Formulation of Problems, Variables, and Focuses in Scientific Research - Muhammad Zaki Rahman; M. Syahran Jailani; Risnita Risnita; Kasful Anwar (Jurnal Indonesia Sosial Sains, 2025)
The formulation of variable problems and focus in research often makes mistakes for researchers of scientific papers. The purpose of this research is to see research techniques and understanding related to formulating problems scientifically, variables and research focuses in a research. The approach in this study uses a literature study approach, data collection techniques that are carried out using documentation from various books and scientific articles that are relevant to the theme raised. In a research, the main main thing of thought and the essential thing is the problem. Research problems that have been identified and limited in order to obtain problems that are worthy of research must still be formulated in order to provide direction for the researcher. A good problem formulation must be able to include and show all variables and the relationship of one variable to another that is to be studied. The source of research problems can be obtained from variables related to problems that are often faced by humans. A problem is a description of the gap between theory and practice, between rules and practice, or between expectations and reality. Problems arise due to challenges, doubts about phenomena, ambiguities, obstacles or gaps. The focus of research is a series of form of problem structure that is described as the center or subject of discussion in a research topic. The focus of this research is expected so that the research has the right focus, so that it is able to collect data and analyze data in accordance with the research objectives.